2010
DOI: 10.1097/anc.0b013e3181d28330
|View full text |Cite
|
Sign up to set email alerts
|

Mothering an Extremely Low Birth-Weight Infant

Abstract: Mothers of preterm infants are reported to experience heightened levels of psychological stress, greater than mothers of full-term infants during the neonatal period. The purpose of this study is to describe the lived experience of what it is like to be a mother of an extremely low birth-weight infant during their stay with their infants in the NICU. Interpretive phenomenology articulated by Benner and Diekelmann is the method of qualitative research employed. Thematic analysis is the method of narrative analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 16 publications
0
52
0
4
Order By: Relevance
“…3,5,28,34 Simply stated, parents find it difficult to carry out parenting activities in the critical care setting. The occurrence of anxiety, depression, fatigue, and sleep disturbance among parents of NICU infants, demonstrated in prior studies, 1,611 was also revealed in the PROMIS measures used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,28,34 Simply stated, parents find it difficult to carry out parenting activities in the critical care setting. The occurrence of anxiety, depression, fatigue, and sleep disturbance among parents of NICU infants, demonstrated in prior studies, 1,611 was also revealed in the PROMIS measures used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The fifth commonality between this study and the findings of Refs. [9,13,16,22] was parents' need for social support, both from their spiritual and biological families as well as from the NICU staff.…”
Section: Discussionmentioning
confidence: 99%
“…As one mother reflecting on the first-time, holding experience described, "I couldn't touch or hold him then. But the next day when we moved over here, they said, yah you can touch him, rub his hand and all that … But that was a wonderful feeling to hold him" ( [22]; p. 90). A second mother stated, "I have been here for her to give her closeness and contact, to make a bond with her.…”
Section: Novicementioning
confidence: 97%
See 1 more Smart Citation
“…There are many sources of stress for mothers in the NICU, including worries about the health of the neonate, exhaustion, and competing obligations at home. 18 Women who give birth prematurely are at higher risk for postpartum depression when compared to women who give birth at term gestation. In a systematic review 19 of 26 studies, which included 2392 mothers of preterm neonates, rates of postpartum depression in the immediate postpartum period were as high as 40%.…”
Section: Impact Of Prematurity On Maternal Mental Healthmentioning
confidence: 99%